THE IMPLEMENTATION OF PROBLEM-BASED LEARNING AND THE KASVOL GAME APPROACH ON STUDENTS’ MOVEMENT COMBINATION SKILLS - Febrianti Gita Hapsari; Agung Wahyudi (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
This study aims to investigate the impact of using animated media on the outcomes of basketball shooting training in children aged 10–11 years. The research employed an experimental method with a population of 40 students participating in basketball extracurricular activities at Cimahi Mandiri 2 Elementary School in Cimahi City. A total sampling technique was used, involving all 40 students. Participants were randomly divided into two groups: an experimental group (20 students) that received training with animated media and a control group (20 students) that received training without animated media. The research instrument used was a basketball shooting test. The results showed that: (a) the use of animated media significantly improved shooting training outcomes, with a t-count of 23.59 > t-table 2.262; (b) training without animated media also led to a significant improvement, with a t-count of 12.68 > t-table 2.262; and (c) the significance test of the difference between group means yielded a t-count of 25.98 > t-table 2.101, indicating a significant difference between the two groups. It is concluded that learning using animated media is more effective in improving basketball shooting performance among elementary school children aged 10–11 years.